Defining Hikikomori between Digital Migration, Ghosting and Cyberactivism. A Netnographic Study on Voluntary Social Self-Isolation in Italy - Coppola, Marianna (Italian Sociological Review, 2022)
The interest in the analysis and study of the phenomenon of withdrawal and processes of “disappearance” from social life face-to-face has grown significantly in recent years both in clinical and in anthropological and sociological fields. The Hikikomori, a phenomenon of voluntary social self-exclusion exploded in Japan in the late nineties of last century, has gradually affected, albeit in different ways, all Western societies coming to become in a few years a real social and health emergency (Ricci, 2009; Saito, 2013). However, recent studies have shown that, although in Japanese society it is considered a social pathology expressly linked to double knit to the supporting structures of Japanese society and its way of understanding the commitment and social confrontation, in Western hybrid forms is considered, instead, an individual condition and in some cases a real psychological-relational structure, imposing a broader reflection on the causes, motivations and coping strategies experienced and implemented by young people who call themselves Hikikomori (Teo, 2015; Bagnato, 2017). The present research aims to analyze, with an avalutative and depathologizing position, the emotional-relational aspects and the processes and ways of socialization of young Italian Hikikomori through the netnographic analysis of the most important online community of Hikikomori in Italy [...]